Urban-rural differential in food consumption in Nigeria: A case study of Ilesa and Atakumosa LGAs of Osun state (2006)
This study focused on the differential in food consumption between urban and rural households in Osun State, Nigeria. The data used in the study were obtained through the use of a structured questionnaire administered to randomly selected food consuming households in the Ilesa and Atakumosa local government areas (LGAs) of Osun State. The analytical tools used include descriptive statistics and ordinary least squares (OLS) regression. The study revealed that urban households have higher levels of per capita food expenditure than their rural counterparts. In addition, household size and the income and educational level of the household head are significant determinants of food consumption among urban dwellers. On the other hand, in rural households, only the income of the household head was significant in determining food consumption.